The relationships between leg peak power and shot-put performance in national-level athletes - Landolsi, M.; Bouhlel, E.; Zarrouk, F.; Lacouture, P.; Tabka, Z. (Isokinetics and Exercise Science, 2014)
AIM: Was to study the relationships between leg peak power, leg muscle volume and Shot-put performance in trained shot-putter. METHODS: Twenty-three shot-putter participated in this study. Anthropometric measurements were carried out to estimate leg muscle volume. Leg peak power and others biomechanical parameters (maximal force, maximal velocity, optimal force, optimal velocity) were measured using leg force-velocity test on ergocycle Monark, and the Optojump device. The shot-put performances were measured during a simulated competition. RESULTS: We found significant correlations between peak power output (W) measured during leg force-velocity Test on ergocycle (PPO-Ergo) and muscle volume for men (r=0.79, p< 0.01) and women (r=0.72, p< 0.05). PPO-Ergo (W, W/kg) was significantly correlated with the vertical jump performance (r=0.56, p< 0.05; r=0.62, p< 0.01 respectively). Shot-put performance was significantly correlated with PPO-Ergo (W, W/kg) and maximal force (N) (r=0.72, p < 0.001; r=0.48, p< 0.05; r=0.85, p< 0.001 respectively). PPO as estimated from the vertical jump using the Optojump system (PPO-Opto) was not correlated to shot-put performances. CONCLUSION: The correlation between PPO-Ergo and shot-put performance showed that the force-velocity Test on ergocycle constitute a useful tool assessing PPO and others biomechanical parameters in shot-putter athletes. However, the Optojump system seems to be not accurate for such subjects. Fat mass constitute probably the limiting factor in shut-putter during this test. ABSTRACT FROM AUTHOR